Influence of hot working on electro slag remelted low alloy steel - Rao A.S.; Prasad V.V.S.; Baligidad R.G.; Rao V.R.; Sarma D.S. (My University, 2025)
A low alloy steel modified with vanadium addition (AISI 4340+V) has been electro slag remelted using calcium fluoride base slag. There was significant reduction of sulphur and oxygen in the metal during ESR. The size and number of nonmetallic inclusions were reduced while the remaining fine inclusions were distributed uniformly in the refined metal. The mechanical properties of cast ESR ingot were comparable to forged electrode in the longitudinal direction and much superior in the transverse direction. The influence of hot working on solidification structure and mechanical proprieties of low alloy steel has ben investigated over a reduction ratio in the of 1:1 to 7:1. Inspite of breaking the cast dendritic structure progressively by hot-forging, there was no significant improvement in tensile properties of ESR steel. However, the impact strength had shown considerable improvement with hot forging.